2018
DOI: 10.1080/09603123.2018.1495322
|View full text |Cite
|
Sign up to set email alerts
|

Сardiovascular mortality during heat waves in temperate climate: an association with bioclimatic indices

Abstract: The authors studied the relative predictive powers of several bioclimatic indices as predictors of population mortality during heat waves. Daily mean and maximum values of air temperature, Humidex, apparent, and physiological equivalent temperatures (PETs) were examined. The numbers of daily deaths and daily meteorological data in Rostov-on-Don (southern Russia) were used. The study period spanned April-September between 1999 and 2011. The eight selected bioclimatic indices were used to identify heat waves and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 38 publications
0
7
0
1
Order By: Relevance
“…First, it was shown that heat (cold) waves were mainly defined as periods with abnormally high (low) temperatures compared to current values, often combined with high humidity (strong wind), which have an adverse effect on human body, expressed in a statistically significant increase in mortality or morbidity [69,71,72,[93][94][95][96][97][98][99][100][101][107][108][109][110][111]. Based on long-term research, it was determined that heat (cold) waves incorporate periods with an excess of the 97(3) % percentile of the distribution of mean daily temperature in the summer (winter) months [145,177].…”
Section: Resultsmentioning
confidence: 99%
“…First, it was shown that heat (cold) waves were mainly defined as periods with abnormally high (low) temperatures compared to current values, often combined with high humidity (strong wind), which have an adverse effect on human body, expressed in a statistically significant increase in mortality or morbidity [69,71,72,[93][94][95][96][97][98][99][100][101][107][108][109][110][111]. Based on long-term research, it was determined that heat (cold) waves incorporate periods with an excess of the 97(3) % percentile of the distribution of mean daily temperature in the summer (winter) months [145,177].…”
Section: Resultsmentioning
confidence: 99%
“…It is necessary and right time to identify the importance of HW and HI, as it helps in understanding the behavior of environmental conditions to live comfortably in a particular region and to reduce mortality and other diseases (Carmona et al 2017;Shartova et al 2018). Keeping this thing in mind; a review on the de nition of HW and equations has been done because of studies done in different continents.…”
Section: Discussionmentioning
confidence: 99%
“…"Equivalent-physiological temperature for a given place" is the air temperature at which for ordinary room conditions the heat balance of the human body remains unchanged with the internal body temperature and skin temperature for a given situation (Hoppe, 1999) This, however, does not mean that this index can not be applied to the open spaces. On the contrary, it helps a person to compare sensations he/she has in the open air with the room conditions that are familiar to him -some evaluations for Russian Federation were described in paper (Shartova et al, 2018).…”
Section: Methodsmentioning
confidence: 99%